Chinese clothing garment, accessory and culture - Hua Mei; Yu hong; Zhang Lei (Beijing China Intercontinental Press, 2017)
In the Chinese way of describing the necessities of life, clothing ranks at the top of "garments, food, shelter and means of travel". In this country with a long history of garments and ornaments, there is a wealth of archeological findings showing the development of garments, as well as their portrayals in ancient mythology, history books, poems and songs, novels and drama. China, as a country made up of 56 ethnic groups that continually influenced each other, has undergone continuous transformation in dress style and customs.
Preface -- A brief history of ancient garments -- Clothes and hierarchy in ancient times -- Silk, the silk road and the art of embroidery -- Beauty of primitive garments -- trends in modern garments -- Appendix : chronological table of the chinese dynasties
Cultural China series : The third volume
Keywords: Costume -- China; Clothing and dress -- China